Bill Clinton : an American journey - Hamilton, Nigel (New York : Random House, 2003)
A biography of America's first baby-boomer president offers an examination of Bill Clinton's background and career, from his Arkansas upbringing and education at Oxford to his early political life.
[1] Great expectations
Includes index.
Includes bibliographical references (p. [747]-752) and index.
82612
Keywords: Clinton, Bill -- 1946- -- Childhood and youth; Presidents -- United States -- Biography; Governors -- Arkansas -- Biography; Interviews -- United States